Analisis Pengaruh Fraud Diamond Terhadap Kecurangan Laporan Keuangan Pada Bank Umum Syariah - Nurun Nadia; Nyata Nugraha; Sartono Sartono (Jurnal Akuntansi dan Governance, 2023)
This study aims to empirically prove the effect of fraud diamonds in the form of pressure, opportunity, rationalization, and capability on the fraudulent financial statements. The data were collected from the financial reports of Islamic Commercial Banks in Indonesia for 2016-2021. And with purposive sampling, 48 samples were established. This study employs multiple linear regression. The results show that pressure and rationalization have positive and significant effect on the fraudulent financial statements, while opportunity and capability have positive but insignificant effect on fraudulent financial statements